Candida Sepsis Following Transcervical Chorionic Villi Sampling - Alona Paz; Roni Gonen; Israel Potasman (Hindawi Limited, 2001)
Background: The use of invasive devices and broad spectrum antibiotics has increased the rate of candidal superinfections.Candida sepsis associated with pregnancy is rare. Candida sepsis following chorionic villi sampling (CVS) has never been reported.